The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12893-021-01437-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of operating room health care professionals' from the challenges of the COVID-19 pandemic

Abstract: Background The operating room nurses have encountered several challenges during the current COVID-19 Pandemic, which subsequently impact their clinical performance. The present study aimed to investigate the experiences of operating room health care professionals' regarding the COVID-19 pandemic challenges in southern Iran. Methods This is a descriptive qualitative study. The required data were collected using in-depth and semi-structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
(27 reference statements)
3
16
0
Order By: Relevance
“…In the study by Gül et al 39 the participating nurses reported that some of the patients who underwent surgery did not undergo PCR testing. The study by Mohammadi et al 40 found that many patients did not have PCR tests before undergoing surgery but were determined to be COVID positive after the surgery. The same study reported that even simple masks were not available for the OR nurses.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Gül et al 39 the participating nurses reported that some of the patients who underwent surgery did not undergo PCR testing. The study by Mohammadi et al 40 found that many patients did not have PCR tests before undergoing surgery but were determined to be COVID positive after the surgery. The same study reported that even simple masks were not available for the OR nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses reported exhaustion; inadequate support from leaders; and inadequate resources, including staff members and equipment. 23 Further, the increased demand for additional nurses and consequent of travel nurses negatively affected safety. Although the use of travel nurses was warranted during the COVID-19 pandemic, safety cultures in facilities were affected by the disruption of clinical care; travel nurses not receiving as much safety education as their resident nurse counterparts; and thwarted work relationships at the facilities, which led to communication errors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a 2021 study aimed at exploring OR personnel's experiences during the COVID‐19 pandemic showed that quality of patient care was affected, stemming from confusion among OR staff members (eg, unpredictability, changes in processes, destabilized workplaces). Nurses reported exhaustion; inadequate support from leaders; and inadequate resources, including staff members and equipment 23 . Further, the increased demand for additional nurses and consequent influx of travel nurses negatively affected safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This variation may be explained in part by differences in rule adherence between physicians and nurses, 8 but suggests that hospitals implementing electronic symptom screening may not automatically comply with relevant government mandates to screen all staff. This variation also likely reduces any efficacy of the system for detecting infections, 5 for epidemiological surveillance, 9 or for reassurance against the stress 10 caused by an inability to socially distance in the operating room.…”
mentioning
confidence: 99%